Fertilidade, caracterização química, mineralogia e morfologia de cerâmicas e solos de terra preta arqueológica do Sambaqui Jacarequara (Barcarena-Pa) - REIS, André Heron Carvalho dos (Universidade Federal do Pará, 2019)
Archaeological Black earth (ABE) are soil stains easily found in archaeological sites. Their dark color and fertility contrasts with adjacent soils, which are usually poor in nutrients. Their formation is related to disposal of organic matter coming from old indian villages, besides the presence of “lítico” artifacts, coal and various ceramic fragments of different styles and traditions. However, researches aimed to evaluate the morfology of the ceramic set, its chemical and mineralogical characteristics and also the assessment of the sambaquis’ fertility still rare. These researches may contribute to a great advance in the knowlegde of ABE and its fertility. In addition, they may elucidate some aspects about the living style of the groups involved. This paper aims to advance in this problematic when analising the ceramic fragments (decorated or not decorated) and the archeo- stratigrafic soil layers (defined by cultural and natural features) from the Sambaqui Jacarequara ABE, in Barcarena, Pará. The samples were submitted to chemical and mineralogical analisis by ICP-MS, ICP-OES, DRX, MEV/EDS, optical microscopy, the assessmente of soil fertility and morfological analises (stylistic and technical aspects) of the sambaqui ceramic set. Regarding to the soils, the obtained data demosntrate and high fertility (V >87 e SB >10), light and strongly basic pH (6,02-8,25), a high concentration of P is avaiable (46,5-818,1 mg/dm3), and the amount of the bases composed predominantly by por Ca e Mg, reflecting the chemical composition of the carbonatic material added. These values are highighted in the layers 2, 3B and 3A with major availability P and Ca, while these values are reduced considerably in the base (Layer 6). The soils are predominantly composed by SiO2, Al2O3, CaO, Fe2O3, K2O e MgO (85, 37 %), which refletcs the mineralogy composed by quartz, calcite, argonite, kaolinite. The concentration of P2O5 is considered low (0, 46 %) when compared with the other ABE in the Amazon, possibly presented in amorphous phase. When confrotating with the crustal avarage is visible the slightly high values of SiO2, CaO, TiO2, P2O5 e MnO. In turn, the ceramics shows basic pH (7, 04-8, 00), high values of sum and base saturation (SB >29, 42; V >94, 7) demosntrating their high fertility level. The P avaiable indicates lower values in the ceramics than in the soil (12-389, 9 mg/dm3 ) displaying the FCs contribution to the soil fertility. Their chemical composition is composed by SiO2, Al2O3, CaO, Fe2O3, K2O, TiO2 P2O5 (75, 33 %). 1 0 Mineralogicaly, the ceramics do not differ from the soil, indicating a local origin to the raw material sources. These ones are composed by quartz phases, musccovite, calcite, argonite, anatase, besides the amorphous phase of metakaolinite, which suggests a burning superior to 550ºC. Crystalline stages related to phosphorus were not found. When confronting chemical data with the ceramics morphology, it is possible to notice that fragments with higher volumetric capacity, fined-grained and lower concentrations of grounded shells in the Clay have a higher concentration of P (> 0,70 %), indicating a possible relation between the materials used during the ceramics fabrication, their use and chemical signature. Morphologically, the results qualified the ceramics in the Regional traditional Mina. However, some variations in the decorative patterns were found between the stratigrafic levels: profile’s basis, one occupation composed by ceramics of introverted forms, fined grained, red engobes e major diversity in the antiplastic use, while from layer 3 there is some ceramics characterized by shells with higher fined-grained, plates with plastic decorations (incised, hand-carved) and fragments much more with the absence od engobe. Therefore, it is concluded that the FCs are fundamental to the maintainance of the fertility of the ABE and also the dissimilarities among chemistry, mineralogy, texture and technology of the ceramics of each layer. It also defines three phases of occupation to the sambaqui: the first phase indicates they would have occupied a promontory of the beach next to the river with the use of aquatics resources in temporary villages; the second one demonstrates a permanent use of the area and intense fishing activity with disposal of organic matter in the soils resulting in the ABE; while the last one demonstrates a post sambaqui occupation with fewer dependence of aquatic resources.